2020
DOI: 10.3390/ijerph17186919
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Frequency of Leukoplakia in Reference of Tobacco Smoking among Northern Polish Population

Abstract: Objective: The aim of the study was an updated analysis of the frequency of leukoplakia in reference to tobacco smoking among the northern Polish population. Material and Methods: Medical records of 5720 patients who suffer from abnormalities and oral mucosa diseases between January 2015–December 2018 were analyzed. Among them, 416 medical charts of patients with leukoplakia were selected. The study group consisted of 196 women and 220 men aged between 21–86 years (average 45.6 years). The analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…OSMF stage 3 could be due to the absence of betel leaf known for its antioxidant properties and proportionately higher dry weight of areca nut with concurrent tobacco use [3] . Whereas lesions like homogenous leukoplakia, smokers melanosis and smokers palate were more prevalent among smokers this finding was compatible with that of Naveen et al( 2016) [9] , Aida Kusiak et al (2020) [21] . Oro-mucosal lesions based on type of tobacco habit revealed that smoking habit was predominantly associated with lesions involving the hard palate like smokers palate this finding was same as that of Saraswathi et al (2006) 22 , whereas smokeless use of tobacco had lesions involving the labial mucosa, buccal and labial vestibule as placement of, consistent with findings of Lesan et al (2013) [15] and Ayo-Yusuf et al (2000) [23] .…”
Section: Discussionsupporting
confidence: 89%
“…OSMF stage 3 could be due to the absence of betel leaf known for its antioxidant properties and proportionately higher dry weight of areca nut with concurrent tobacco use [3] . Whereas lesions like homogenous leukoplakia, smokers melanosis and smokers palate were more prevalent among smokers this finding was compatible with that of Naveen et al( 2016) [9] , Aida Kusiak et al (2020) [21] . Oro-mucosal lesions based on type of tobacco habit revealed that smoking habit was predominantly associated with lesions involving the hard palate like smokers palate this finding was same as that of Saraswathi et al (2006) 22 , whereas smokeless use of tobacco had lesions involving the labial mucosa, buccal and labial vestibule as placement of, consistent with findings of Lesan et al (2013) [15] and Ayo-Yusuf et al (2000) [23] .…”
Section: Discussionsupporting
confidence: 89%
“…There is a known significant correlation between tobacco smoking and the presence of oral leukoplakia. Kusiak et al [45] in the group of 416 subjects with leukoplakia found its highest incidence in the age group of 41-60 years. In addition, in 85.1% cases, they were active smokers.…”
Section: Discussionmentioning
confidence: 94%
“…Although the case number and incidence of OL in females were not as large as for males, the postoperative recurrence and development of malignant change of OL in female patients could be as serious as in male patients. From a gender perspective, "female" has been regarded as a risk factor for malignant transformation of OL in some studies [13][14][15][16][17][18], but "male" has not. Reviewing the literature about the research on OL, neither malignant transformation of OL focusing solely on female patients nor comparison of treatment outcomes between both genders has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the analysis of OL undergoing malignant transformation, old age, female gender, area of leukoplakia exceeding 200 mm 2 , non-homogeneous type, and higher grades of dysplasia were reported to be risk factors [11,12]. Although female gender has been reported as an associated factor related to transformation to carcinoma [13][14][15][16][17][18], there were opposite perspectives on the role of female gender as a risk factor related to malignant transformation of OL [19]. The null hypothesis is that there is no difference of risk of malignant transformation of OL between the female patients and male patients.…”
Section: Introductionmentioning
confidence: 99%